'Stakes and strategies': Orientation Report. (4th August 2014) - Anon,
This article reproduces the text of the Orientation Report prepared by Federation Internationale de l'Automobile (FIA) for the World Automobile Convention, held in Paris, 18–20 April 1989. The document briefly outlines the worldwide politico–economic context within which the medium–term future of the motor car and its industry lies; the main problems facing all the parties involved, including the people responsible for preparing this future; and the suitable solutions that may be envisaged to solve these problems.